A wide area fault detection algorithm for transmission networks equipped with series compensation units - Mohamed A. Ebrahim; Fady Wadie; Mousa A. Abd-Allah (International Journal of Applied Power Engineering (IJAPE), 2019)
In this paper, a wide area back-up protection (WABP) algorithm is presented based on phasor measurement units (PMUs) measurements placed across the transmission network. The proposed algorithm computes a selected index named as positive sequence power index (PSPI) to detect faults in the network. Firstly, the network is subdivided into back-up protection zones. For each zone, the PSPI index is computed as absolute the value of the difference between the positive sequence sent and received phasor powers across the terminals of the zone. For each zone, the PSPI is compared to a predefined threshold to detect faults. One of the contributions in this paper is the usage of mathematical formulation to set the threshold values for each zone rather than experimental trials usually used in previous literature. In addition, the algorithm doesn’t depend iterative solutions nor line parameters of the network as usually used in WABP schemes. These advantages enhance the degree of confidence in decisions of the algorithm and reduces computational burdens to trivial amount. The presented algorithm (Level-1) could be enhanced into (level-2) if PMUs are available on all buses and in such case, the faulty line could be detected directly in a single step. WSCC 9-bus system and NE 39-bus systems were considered to accomplish this study. Severe cases for series compensated lines were taken into consideration including voltage or current inversion. Simulation results emphasis on algorithm’s robustness and adaptability.